Early detection of resistance to Mycosphaerella fijiensis in local genotypes of Musa in Ecuador - García, Galo Cedeño (2017)
The aim of this research was to determine resistance reaction of 14 Musa genotypes against Mycosphaerella fijensis, causal agent of Black Sigatoka disease. Two experiments were conducted in laboratory and shadehause at Pichilingue research Station from the National Institute of Agricultural Research (INIAP), Ecuador. Genotypes considered were: Orito (AA), Guineo de jardín, Williams, Filipino, Gross Mitchel, Mulato and Morado, (AAA); Limeño, Maqueño, Dominico, Dominico-Hartón, Dominico gigante, Dominico negro and Barraganete from the AAB genome. Two inoculation methods were used to asses’ resistance: a) in vitro inoculation over leaf fragments with a conidial suspension, and b) inoculation of eight weeks old seedlings with a mycelial suspension of the fungus. In the first case, the incubation period (IP) and the number of lesions at 14 and 20 days after inoculation (DDI) were measured. For in vitro trial, the incubation period (IP) and the number of leaf lesions 14 and 20 days after inoculation (DDI) were measured, and for seedlings, PI, period of symptoms evolution (TES) and time for disease development (TDE) were recorded. Statistically significant (p ≤ 0.05) differences were found for all variables. Cultivars Orito (AA) and Limeño (AAB) qualify as resistant while all the others were susceptible, though response to inoculation within the latter group showed a range of variability.